2022
DOI: 10.1186/s13613-022-01052-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of dexmedetomidine in patients with sepsis: a systematic review and meta-analysis of randomized-controlled trials

Abstract: Background Dexmedetomidine is widely used in patients with sepsis. However, its effect on septic patients remains controversial. The objective of this study was to summarize all randomized controlled trials (RCTs) examining dexmedetomidine use in sepsis patients. Methods This systematic review and meta-analysis included RCTs comparing dexmedetomidine with other sedatives in adult sepsis patients. We generated pooled relative risks (RRs) and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
2
6
1
3
Order By: Relevance
“…Cox proportional hazards regression results also supported that dexmedetomidine was related to lower 28-day mortality. These results were consistent with previous studies ( Song et al, 2019 ; Aso et al, 2021 ; Zhang et al, 2022 ). However, the DESIRE trial indicated that dexmedetomidine treatment did not improve 28-day mortality in patients requiring mechanical ventilation with sepsis ( Kawazoe et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…Cox proportional hazards regression results also supported that dexmedetomidine was related to lower 28-day mortality. These results were consistent with previous studies ( Song et al, 2019 ; Aso et al, 2021 ; Zhang et al, 2022 ). However, the DESIRE trial indicated that dexmedetomidine treatment did not improve 28-day mortality in patients requiring mechanical ventilation with sepsis ( Kawazoe et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…There was no significant difference in outcomes between the septic adults treated with DEX and those treated with propofol [ 63 ]. However, a recent meta-analysis of 19 randomized controlled trials that enrolled 1929 patients showed the benefit of DEX in septic patients [ 64 ]. Future randomized controlled trials need to identify the population of patients with sepsis who can benefit most from DEX and its optimal regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Morelli et colleagues demonstrated that using dexmedetomidine for the sedation of septic patients guarantees a comparable level of sedation and reduces the dosage of norepinephrine required compared to propofol ( 68 ), and from a recent meta-analysis resulted that dexmedetomidine, in human patients with sepsis, could significantly reduce mortality compared with benzodiazepines but not with propofol ( 69 ).…”
Section: Dexmedetomidine In Critical Patientsmentioning
confidence: 99%